1997
DOI: 10.1093/humrep/12.11.2373
|View full text |Cite
|
Sign up to set email alerts
|

Oral misoprostol for cervical priming in non-pregnant women

Abstract: Endometrial biopsy and hysteroscopy are important investigations in women presenting with abnormal vaginal bleeding. Endometrial biopsy is often performed as an outpatient procedure by endometrial aspiration. Difficulty in entering the internal cervical os may be encountered, especially in nulliparous women. The same problem may occur during hysteroscopy or dilatation and curettage. It is well known that use of a cervical priming agent is effective in reducing complications during cervical dilatation in pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
2
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 0 publications
0
56
2
6
Order By: Relevance
“…We empirically chose 800 mg as the study dose because we expect the degree of drug absorption to be less in menopausal women. Ngai et al 5 , with the dosage of 400 mg orally, did not report any significant side effect. Although there was no literature suggesting the optimal dose for this group of patients it seemed that this dosage is acceptable with low incidence of side effects.…”
Section: Discussionmentioning
confidence: 89%
“…We empirically chose 800 mg as the study dose because we expect the degree of drug absorption to be less in menopausal women. Ngai et al 5 , with the dosage of 400 mg orally, did not report any significant side effect. Although there was no literature suggesting the optimal dose for this group of patients it seemed that this dosage is acceptable with low incidence of side effects.…”
Section: Discussionmentioning
confidence: 89%
“…These beneficial effects on cervical ripening makes it also a desirable agent for helping cervical dilatation on non-pregnant women. Ngai et al (1997) had reported misoprostol usage on non-pregnant women. Following this study many reports had supported its beneficial effects on cervical dilatation.…”
Section: Discussionmentioning
confidence: 99%
“…These studies did not find a significant ripening effect of misoprostol compared with placebo. 1,11,16 Two earlier studies have suggested that misoprostol is effective for cervical ripening in postmenopausal women but both studies included postmenopausal women as a subgroup in their analysis. 10,11 Atmaca et al studied the ripening effect of misoprostol on estrogen pretreated cervix in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…These include creation of false passage, difficulty in entering the internal os, cervical tear, hemorrhage, uterine perforation etc 1 The incidence of these complications can be reduced if cervix is ripened before the procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation